Opera and modern culture : Wagner and Strauss - Kramer, Lawrence, 1946- (University of California Press, 2004)
Musicologist Lawrence Kramer argues that for the past two centuries the preoccupation of a group of famous operas with the limits of supremacy & debasement has come to define a normality that is the very opposite of the operatic.